Agriculture and economic transformation in the Middle East and North Africa: A review of the past with lessons for the future - Nin-Pratt, Alejandro; El-Enbaby, Hoda; Figueroa, Jose Luis; ElDidi, Hagar; Breisinger, Clemens (International Food Policy Research Institute, 2018)
The agriculture sector is key for economic and social development, but the sector’s potential has not received enough attention from policy makers and stakeholders in the Middle East and North Africa (MENA) region. Political transitions, instability, and the resulting refugee crisis have shifted focus away from other pressing development challenges, including slow progress in economic diversification, high unemployment, and persistent high food insecurity and rural poverty. Despite its small contribution to GDP, agriculture is strategic for sustainable development in the MENA countries. Agriculture, for example, is central to achieve food and water security in a region characterized as one of the most food insecure and water scarce in the world. The sector’s role in employment is also central, given the region’s high structural unemployment. However, it will not be possible for MENA countries to develop agriculture without a pathway to structural economic transformation. The region has already started the process of transformation but longstanding challenges remain. This report aims to examine the drivers, constraints, and social implications of agricultural development in MENA and to explore possible cornerstones for new and sustainable development strategies in the context of economic transformation. More specifically, the report provides answers to the following questions: • What development strategies and policies did governments in MENA put in place over the past three decades and how did they affect the performance of agriculture? • How did the structural characteristics of the MENA countries affect agricultural development and the economic transformation process in the region? • What did we learn from the past performance of agriculture? What should be the central elements guiding future agricultural policies? • What are elements of a new and sustainable development strategy in MENA countries? • What is the role of agriculture and agro-industries for development in MENA?